THE RELATIONSHIP OF THE WATER PARAMETER TO THE GROWTH AND THE CARRAGEENAN QUALITY OF Kappaphycus alvarezii (DOTY) DOTY EX P.C. SILVA (1996) IN BELOPA, LUWU REGENCY, INDONESIA - Istiqamah, Nur; Litaay, Magdalena; Ambeng, Ambeng (Indonesian Aquaculture Journal, 2025)
The research aims to determine the relationship of water quality parameters to the growth and carrageenan quality of red algae Kappaphycus alvarezii. This research was conducted in July November 2022 in the waters of Belopa sub-district, South Sulawesi, Indonesia. Water quality parameters measured were temperature, pH, salinity, brightness, depth, current velocity, dissolved oxygen, nitrate, and phosphate. The cultivation was conducted by longline method. There were 3 stations and each station had 3 stretched ropes with a length of 5 m as replicates. The growth was calculated by measuring the specific growth rate and the absolute weight growth. The quality of carrageenan was tested by yield, water content, and ash content. Water quality and growth data were collected every 10 days for 40 days. The effect of growth and quality of carrageenan on each location was analyzed through ANOVA and Kruskal Wallis tests. The relationship between parameters was analyzed through coefficient correlation tests (Pearson Simple Linear Correlation). The determination of characteristic parameters at each station was applied through the principal component analysis test. The results showed that the yield of carrageenan was impacted by phosphate. The water affected by nitrate and brightness. Ash content affected by temperature, pH, and current velocity. Different location  did not significantly affect the growth and quality of carrageenan.